New version of near pen-side diagnostic assay, a diagnostic tool farmers or meat inspectors in Kenya and Uganda could use to detect Taenia solium cyst infections (cysticercosis) in pigs - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
In 2018, the innovation reached end of piloting, but based on poor results, it moved back into proof of concept with a different partner. Now in 2021, a second version of the penside test was developed and tested in the field in two countries and is demonstrating promising results.